PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS SUSTAINABILITY REPORT PADA PERUSAHAAN DALAM INDUSTRI BERPROFIL TINGGI (HIGH-PROFILE INDUSTRIES) (Studi Empiris pada Perusahaan dalam Industri Berprofil Tinggi (High-Profile Industries) yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024) - Daffa Satria Kriezna Putra; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the impact of good corporate governance (GCG) on the quality of sustainability reports of high-profile industry (High-Profile Industries) firms listed on the Indonesia Stock Exchange (IDX) over the 2022–2024 period. The dependent variabel is sustainability report quality, measured using Bloomberg’s ESG Disclosure Score. The GCG variabels are proxied by board independence, gender diversity on the board of directors, the audit committee, the sustainability committee, and managerial ownership. This study also applies control variabels, namely industry characteristics and leverage measured by the debt-to-asset ratio (DAR). Using purposive sampling, the study obtained a total of 243 firm-year observations from high-profile industry firms listed on the IDX during the study period. Secondary data were collected from companies’ annual reports and/or sustainability reports, IDX disclosures, and Bloomberg data based on the predetermined criteria. Hypotheses were tested using multiple linear regression analysis. The findings indicate that board independence, the audit committee, and the sustainability committee have a positive and significant effect on sustainability report quality. Gender diversity on the board of directors shows a negative and significant effect on sustainability report quality. In contrast, managerial ownership has a negative but insignificant effect, leverage (DAR) does not have a significant effect, and industry characteristics have a positive and significant effect on sustainability report quality.